Hubungan Karakteristik Terhadap Sikap Mengkonsumsi Tablet Fe Dengan Kejadian Anemia Pada Ibu Hamil Di Puskesmas Tanjung Tiram Kabupaten Batu Bara Provinsi Sumatera Utara Tahun 2022 - Fitri Handayani; Eka Purnama; Humaida Hanim; Marlina Simbolon (Jurnal Anestesi, 2024)
Anemia is a condition where the body has too few red blood cells (erythrocytes), where the red blood cells contain hemoglobin which functions to carry oxygen to all body tissues (Nugroho, 2014). During pregnancy there is an increase in blood volume or also called as (hypervolemia). In pregnant women, anemia increases the frequency of complications in pregnancy and childbirth. During pregnancy, if anemia cannot be treated until the end of pregnancy, it will affect the postpartum period. The current government program to prevent anemia is to give pregnant women a minimum of 90 iron tablets during pregnancy containing 320 mg FeSO4 (60 mg iron and 0.25 mg folic acid). This program aims to prevent and overcome the incidence of anemia in pregnant women. This type of research is analytical research with a cross sectional design, namely the researcher takes samples from a population using a questionnaire as a data collection tool where the sample size is 46 pregnant women. From the results of the cross tabulation, it shows that the parity variable on the incidence of anemia in pregnant women obtained statistical test results with a p value = 0.005, meaning that there is a significant relationship between parity and the incidence of anemia in pregnant women at the Tiram Community Health Center, Tiram District, Batu Bara Regency, North Sumatra Province. 2022. Based on the research results of the knowledge variable on the incidence of anemia in pregnant women, statistical test results were obtained with a value of p value = 0.000, meaning that there is a significant relationship between knowledge and the incidence of anemia in pregnant women in the Tiram District Health Center, Tiram District, Batu Bara Regency, North Sumatra Province. 2022. Based on the research results of the variable compliance with the consumption of Fe tablets on the incidence of anemia in pregnant women, statistical test results were obtained with a p value = 0.007, meaning that there was a significant relationship between compliance with the consumption of Fe tablets and the incidence of anemia in pregnant women in the Tiram Village Community Health Center, Tiram District, Batu Bara Regency. North Sumatra Province in 2022 Conclusion: From a total of 46 respondents as a result of research on the variables of parity, knowledge and compliance, there is a significant relationship to the incidence of anemia in pregnant women in the Tiram Village Community Health Center, Tiram District, Batu Bara Regency, North Sumatra Province in 2022.